ANTI-TIPPING OFF PERSPECTIVE TO TARGET COMPANY BANK’S SUSPICIOUS TRANSACTION REPORT IN MERGER ACTIVITY - Muh. Afdal Yanuar (Program magister Kenotariatan Fakultas Hukum Universitas Lambung Mangkurat, 2021)
The purpose of this study is, to explain the legal concept and regulation of anti-tipping off in the banking sector, and to explore about the position of the Suspicious Transaction Report belonging to the target company bank in the merger activity based on anti-tipping off provisions. This is Normative legal Research with a statutory approach, a conceptual approach and a comparative approach. The background of the problem in this paper is, there is no strong legitimacy about definition and limitation of the meaning of the phrase ‘other parties’ in article 12 paragraph (1) Anti Money Laundering Law, which regulate about anti tipping off, wether the absorbing company bank is the ‘other parties’ of target company bank on the merger activity or not, when target company bank delivered it suspicious transaction reports to absorbing company bank prior to the merger. The results and discussion concluded that Anti-tipping off is a provision that prohibits tipping off. Tipping off itself is an action by a senior officer or Management or Employee of the Reporting Party (inter alia, Bank) to disclose facts related to a Suspicious Transaction Report that has been reported to Financial Intelligence Unit (in casu, PPATK). This is concrete and manifested in the provisions of Article 12 paragraph (1) of the Anti Money Laundering Law. Besides that, Viewed from the anti-tipping off perspective, all the rights owned by the target company Bank prior to the merger, ex officio, become the rights of the absorbing company, since the target company Bank legally merges into a part of the absorbing company. Based on that, it can be concluded that with respect to merger activities, the absorbing company banks are not ‘other Parties’ from the target company Bank